A low-sidelobe and wideband dual linearly polarized array antenna for UAV SAR application in X-band. Issue 2 (22nd January 2022) - Lim, Seong-Ju; Kim, Jeong-Wook; Kim, Sol; Cho, Hyunyoung; Yu, Jong-Won; Lee, Woo-Kyung
Abstract : In this letter, a 4 × 6 microstrip patch array antenna with a low sidelobe level (SLL) for dual linearly polarized synthetic aperture radar (SAR) is proposed. The low SLL in wide-band is obtained by implementing the Chevyshev taper distribution. An optimal approach to design an unequal-power symmetric microstrip divider for dual-polarization is employed in the same layer with high isolation between the polarizations. The proposed antenna consists of squared patches excited by aperture coupled slots. With the analysis of resolution, swath, and noise equivalent sigma zero (NESZ) of the SAR system, we selected the antenna parameters such as bandwidth, beamwidth, gain, and SLL. The proposed antenna has a more than 10 % bandwidth and peak gains of 18.2 dBi and 18.3 dBi in V and H-polarization, respectively. The measured SLL in both polarizations are under −21.1 dB in the E-plane and −17.0 dB in the H-plane at the 10 GHz.